Tim GTLN: a/ A = 2 – x^2 – y^2 – 2(x + y) b/ B = -4x^2 + 4x + 3 18/07/2021 Bởi Serenity Tim GTLN: a/ A = 2 – x^2 – y^2 – 2(x + y) b/ B = -4x^2 + 4x + 3
Đáp án: a, Ta có : `A = 2 – x^2 – y^2 – 2(x + y)` `= -[x^2 + 2(x + y) + y^2 – 2]` `= -(x^2 + 2x + 2y + y^2 – 2)` `= -[(x^2 + 2x + 1) + (y^2 + 2y + 1) – 4]` `= -[(x + 1)^2 + (y + 1)^2] + 4 ≤ 4` Dấu “=” xẩy ra <=> $\left \{ {{x + 1 = 0} \atop {y + 1 = 0}} \right.$ <=> $\left \{ {{x = -1} \atop {y = -1}} \right.$ Vậy GTLN của A là `4 <=> x = y = -1` b, Ta có : `B = -4x^2 + 4x + 3` `= -(4x^2 – 4x – 3)` `= -[(2x)^2 – 2.2x.1 + 1 – 4]` `= -(2x – 1)^2 + 4 ≤ 4` Dấu “=” xẩy ra `<=> 2x- 1 = 0` `<=> x = 1/2` Vậy GTLN của B là `4 <=> x = 1/2` Giải thích các bước giải: Bình luận
Đáp án:
a, Ta có :
`A = 2 – x^2 – y^2 – 2(x + y)`
`= -[x^2 + 2(x + y) + y^2 – 2]`
`= -(x^2 + 2x + 2y + y^2 – 2)`
`= -[(x^2 + 2x + 1) + (y^2 + 2y + 1) – 4]`
`= -[(x + 1)^2 + (y + 1)^2] + 4 ≤ 4`
Dấu “=” xẩy ra
<=> $\left \{ {{x + 1 = 0} \atop {y + 1 = 0}} \right.$
<=> $\left \{ {{x = -1} \atop {y = -1}} \right.$
Vậy GTLN của A là `4 <=> x = y = -1`
b, Ta có :
`B = -4x^2 + 4x + 3`
`= -(4x^2 – 4x – 3)`
`= -[(2x)^2 – 2.2x.1 + 1 – 4]`
`= -(2x – 1)^2 + 4 ≤ 4`
Dấu “=” xẩy ra
`<=> 2x- 1 = 0`
`<=> x = 1/2`
Vậy GTLN của B là `4 <=> x = 1/2`
Giải thích các bước giải: